1997
DOI: 10.1037/0022-3514.72.3.581
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of intelligence in leaderless groups: The dynamic effects of shyness and acquaintance.

Abstract: Perceptions of intelligence were investigated in 2 longitudinal studies of leaderless discussion groups (LDGs). In Study 1 (N = 87), students completed trait-shyness questionnaires and met 7 times in groups of 4-5. After Meetings 2 and 7, participants rated all group members on state shyness and intelligence. Trait-shy participants were initially judged to be less intelligent on both self-and peer ratings. At Time 2, however, trait-shy participants were no longer derogated by peers. Study 2 (N = 103) replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 51 publications
4
61
0
1
Order By: Relevance
“…In particular, much remains to be learned about how and why certain impressions change as they mature (for exceptions see Felmlee, 1995;Paulhus & Morgan, 1997;Rydell & McConnell, in press;Swann, Milton, & Polzer, 2000). Current explanations for impression stability and instability in Big Five domains have focused on the abundance of behavioral cues readily available to the perceiver (John & Robins, 1993).…”
Section: Discussionmentioning
confidence: 97%
“…In particular, much remains to be learned about how and why certain impressions change as they mature (for exceptions see Felmlee, 1995;Paulhus & Morgan, 1997;Rydell & McConnell, in press;Swann, Milton, & Polzer, 2000). Current explanations for impression stability and instability in Big Five domains have focused on the abundance of behavioral cues readily available to the perceiver (John & Robins, 1993).…”
Section: Discussionmentioning
confidence: 97%
“…As with other psychiatric disorders, social phobia-related difficulties extend beyond the individual: while it has been stressed that social anxiety may arise from the reactivation of relational knowledge based on negative experiences with significant others, it has also been shown that social anxiety, in turn, impairs interpersonal relationships and that it is, therefore, associated with fewer and more negative social relationships at all stages of life. For instance, shy individuals are seen as less intelligent than non-shy people during initial interactions, even though there is no actual association between social anxiety and intelligence [116]. Apart from negative responses by others' towards individuals with social anxiety, it is a matter of some debate whether interpersonal problems on the side of the patient are primarily related to social skill deficits or constitute self-protective strategies [117].…”
Section: (D) the Case Of Schizophreniamentioning
confidence: 99%
“…What are the cues people are using to ascertain how much information someone knows about politics? Research on perceptions of intelligence suggests individuals use very basic cues-sometimes as simple as whether an individual wears glasses-to determine who is and who is not an expert (Murphy et al 2003;Paulhus and Morgan 1997;Zebrowitz et al 2002).…”
mentioning
confidence: 99%